OPTIMALISASI OBJEK CITRA DENGAN METODE KETETANGGAAN PIKSEL DAN PERERATAAN HISTOGRAM - Pangaribuan, Hotma; Sitohang, Sunarsan (JURSIMA, 2025)
Digital image is a very important branch of science in processing two-dimensional and three-dimensional images. Digital images are used to view and analyze an image from pixel operations with the image histogram method, the purpose of this study is to determine image optimization using pixel neighborhoods and Histogram averaging and to determine image comparisons using pixel neighborhood methods and Histogram averaging?. While the images used include black and white images (binary), grayscale images and colored images. The method used is the histogram method, which is useful for observing the distribution of color intensity and can be used for decision making, for example in increasing brightness or stretching contrast and color distribution, Useful for determining boundaries in separating objects from their backgrounds, Providing a percentage of color composition and texture intensity for the purpose of image identification. Especially for colored images, histograms can be applied to a combination of RGB components or per component.